Chaperones and their role in telomerase ribonucleoprotein biogenesis and telomere maintenance - Viviescas, Maria Alejandra [UNESP]; Cano, Maria Isabel Nogueira [UNESP]; Segatto, Marcela [UNESP] (Elsevier, 2019)
Telomere length maintenance is important for genome stability and cell division. In most eukaryotes, telomeres are maintained by the telomerase ribonucleoprotein (RNP) complex, minimally composed of the Telomerase Reverse Transcriptase (TERT) and the telomerase RNA (TER) components. In addition to TERT and TER, other protein subunits are part of the complex and are involved in telomerase regulation, assembly, disassembly, and degradation. Among them are some molecular chaperones such as Hsp90 and its co-chaperone p23 which are found associated with the telomerase RNP complex in humans, yeast and probably in protozoa. Hsp90 and p23 are necessary for the telomerase RNP assembly and enzyme activity. In budding yeast, the Hsp90 homolog (Hsp82) is also responsible for the association and dissociation of telomerase from the telomeric DNA by its direct interaction with a telomere end-binding protein (Cdc13), responsible for regulating telomerase access to telomeres. In addition, AAA+ ATPases, such as Pontin and Reptin, which are also considered chaperone-like proteins, associate with the human telomerase complex by the direct interaction of Pontin with TERT and dyskerin. They are probably responsible for telomerase RNP assembly since their depletion impairs the accumulation of the complex. Moreover, various RNA chaperones, are also pivotal in the assembly and migration of the mature telomerase complex and complex intermediates. In this review, we will focus on the importance of molecular chaperones for telomerase RNP biogenesis and how they impact telomere length maintenance and cellular homeostasis.
Keywords: Biogenesis; Chaperones; Quadruplex structure; Ribonucleoprotein complex; Telomerase; Telomeres